The relation between intercultural Sensitivity and world music preferences Among grammar school and vocational School students - Petrušić, Daniela; Šešelj, Tonka (Revija za elementarno izobraževanje, 2021)
The paper explores the influence of the type of secondary education chosen by the participants on the level of intercultural sensitivity and world music preferences, as well as the connection between intercultural sensitivity and world music preferences. The research employed a general data questionnaire, the Intercultural Sensitivity Scale and an assessment scale to examine music fragment preferences in a sample of 124 participants. The results have significant implications for music and pedagogical theory and practice, in terms of increasing intercultural sensitivity and the tolerance of students towards members of other cultures and their music.
Keywords: music pedagogy; intercultural sensitivity; musical preferences; world music; music education